Measurement of the Higgs boson coupling properties in the H → ZZ ∗ → 4ℓ decay channel at √s=13 TeV with the ATLAS detector - Santos, S. P. Amor dos (2018)
The coupling properties of the Higgs boson are studied in the four-lepton (e, μ) decay channel using 36.1 fb−1 of pp collision data from the LHC at a centre-of-mass energy of 13 TeV collected by the ATLAS detector. Cross sections are measured for the main production modes in several exclusive regions of the Higgs boson production phase space and are interpreted in terms of coupling modifiers. The inclusive cross section times branching ratio for H → ZZ∗ decay and for a Higgs boson absolute rapidity below 2.5 is measured to be 1. 73− 0.23 + 0.24(stat.)− 0.08 + 0.10(exp.) ± 0.04(th.) pb compared to the Standard Model prediction of 1.34±0.09 pb. In addition, the tensor structure of the Higgs boson couplings is studied using an effective Lagrangian approach for the description of interactions beyond the Standard Model. Constraints are placed on the non-Standard-Model CP-even and CP-odd couplings to Z bosons and on the CP-odd coupling to gluons.